2010
DOI: 10.1152/ajpheart.00682.2009
|View full text |Cite
|
Sign up to set email alerts
|

H2S ameliorates oxidative and proteolytic stresses and protects the heart against adverse remodeling in chronic heart failure

Abstract: Mishra PK, Tyagi N, Sen U, Givvimani S, Tyagi SC. H2S ameliorates oxidative and proteolytic stresses and protects the heart against adverse remodeling in chronic heart failure. Am J Physiol Heart Circ Physiol 298: H451-H456, 2010. First published November 20, 2009; doi:10.1152/ajpheart.00682.2009.-Reactive oxygen and nitrogen species (ROS and RNS, respectively) generate nitrotyrosine and activate latent resident myocardial matrix metalloproteinases (MMPs). Although in chronic heart failure (CHF) there is robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 25 publications
5
83
0
Order By: Relevance
“…As mentioned above, CSE/H 2 S has been implicated to be an endogenous antioxidative stress system in myocardium. 18,19) Our study also showed that exercise could increase CSE expression. As the CSE level positively correlates to T-AOC and inversely correlates to MDA in the myocardium of OVX rats and overexpression of CSE prevented ISO-induced damage in cardiomyocytes in vitro, we believe that exercise training improvement of oxidative stress status may be through the increase of CSE expression in the myocardium of OVX rats.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As mentioned above, CSE/H 2 S has been implicated to be an endogenous antioxidative stress system in myocardium. 18,19) Our study also showed that exercise could increase CSE expression. As the CSE level positively correlates to T-AOC and inversely correlates to MDA in the myocardium of OVX rats and overexpression of CSE prevented ISO-induced damage in cardiomyocytes in vitro, we believe that exercise training improvement of oxidative stress status may be through the increase of CSE expression in the myocardium of OVX rats.…”
Section: Discussionsupporting
confidence: 61%
“…The CSE/H 2 S system has been implicated as one of the endogenous anti-oxidative stress factors in cardiomyocytes. 19,24) It has been shown that H 2 S acts as a direct scavenger of reactive oxygen species (ROS) and peroxynitrite and enhances mitochondrial Mn-SOD activity. 25,26) One of our previous studies demonstrated that the level of CSE and H 2 S generation correlated to T-AOC in myocardium of OVX rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After being treated with NaHS in shunt group, TIMP-1 mRNA expression was significantly reduced. Furthermore, we found similar changes in TIMP-1 protein expression levels, which is consistent with a previous report [29] . When NaHS was administered to the sham group, no difference in TIMP-1 expression was observed.…”
Section: Discussionsupporting
confidence: 93%
“…This leads to apoptosis and causes transition from compensatory cardiac hypertrophy to decompensatory heart failure (41). Recent studies report that the endogenous gaseous transmitter, hydrogen sulfide (H 2 S) plays an important role in cardiac protection during ischemia, infarction and heart failure (108,116,(148)(149). H 2 S is endogenously generated by pyridoxal-5' phosphate dependent enzymes, cystathione ~ synthase (CBS) and cystathione V lyase (CSE) using L-cysteine as a substrate (103).…”
Section: Role Of Hydrogen Sulfide During Transition From Cardiac Hypementioning
confidence: 99%